Chesapeake (Frigate) logbook - Chesapeake (Frigate)
Logbook (1807 May 9-1809 February 21; 205 pages) of the frigate Chesapeake. Entries relate to weather and sea conditions, the Chesapeake's encounter with the British warship Leopard, the removal of James Barron as commanding officer, and the taking of command by Capt. Stephen Decatur.
Microfilm edition available
Microfilm edition produced from original in Manuscript Division.
Collection material in English.
Keywords: Barron, James, -- 1769-1851.; Decatur, Stephen, -- 1779-1820.; Leopard (Warship); Ship's papers -- 19th century; Great Britain -- History, Naval -- 19th century; United States -- History, Naval -- To 1900.